Interaction of an anticancer peptide fragment of azurin with p53 and its isolated domains studied by atomic force spectroscopy - Bizzarri AR; Santini S; Coppari E; Bucciantini M; Di Agostino S; Yamada T; Beattie CW; Cannistraro S (International Journal of Nanomedicine, 2011)
Anna Rita Bizzarri1, Simona Santini1, Emilia Coppari1, Monica Bucciantini2, Silvia Di Agostino3, Tohru Yamada4, Craig W Beattie4, Salvatore Cannistraro11Biophysics and Nanoscience Centre, CNISM, Facoltà di Scienze, Università della Tuscia, Viterbo, 2Department of Biochemical Sciences, University of Florence, Florence, 3Molecular Oncogenesis Laboratory, Experimental Oncology Department, Regina Elena Cancer Institute, Rome, Italy; 4Department of Surgical Oncology, University of Illinois College of Medicine, Chicago, IL, USAAbstract: p28 is a 28-amino acid peptide fragment of the cupredoxin azurin derived from Pseudomonas aeruginosa that preferentially penetrates cancerous cells and arrests their proliferation in vitro and in vivo. Its antitumor activity reportedly arises from post-translational stabilization of the tumor suppressor p53 normally downregulated by the binding of several ubiquitin ligases. This would require p28 to specifically bind to p53 to inhibit specific ligases from initiating proteosome-mediated degradation. In this study, atomic force spectroscopy, a nanotechnological approach, was used to investigate the interaction of p28 with full-length p53 and its isolated domains at the single molecule level. Analysis of the unbinding forces and the dissociation rate constant suggest that p28 forms a stable complex with the DNA-binding domain of p53, inhibiting the binding of ubiquitin ligases other than Mdm2 to reduce proteasomal degradation of p53.Keywords: AFS, cancer physics, unbinding forces